2022
DOI: 10.3390/ijerph19159604
|View full text |Cite
|
Sign up to set email alerts
|

Injurious Memories from the COVID-19 Frontline: The Impact of Episodic Memories of Self- and Other-Potentially Morally Injurious Events on Romanian Nurses’ Burnout, Turnover Intentions and Basic Need Satisfaction

Abstract: Nurses have been frequently exposed to Potentially Morally Injurious Events (PMIEs) during the COVID-19 pandemic. Due to resource scarcity, they both perpetrated (self-PMIEs) and passively witnessed (other-PMIEs) moral transgressions toward the patients, severely violating their moral values. Our study investigated the impact of self- and other-PMIEs on work outcomes by exploring nurses’ episodic memories of these events and the basic psychological need thwarting associated with them. Using a quasi-experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 103 publications
(275 reference statements)
1
17
0
Order By: Relevance
“…Maslach and Leiter [ 19 ] suggested that emotional exhaustion and depersonalization must be contained in the measurement of burnout, and prolonged emotional exhaustion can lead to depersonalization. Previous research on nurses’ burnout indicated that workload [ 20 ], job strain [ 9 , 10 , 11 ], morally injurious events [ 21 ], anxiety, and depression [ 22 ] positively affected burnout. Nurses with high levels of burnout were more prone to have higher turnover intention [ 23 , 24 ], lower job satisfaction [ 25 ] and organizational commitment [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maslach and Leiter [ 19 ] suggested that emotional exhaustion and depersonalization must be contained in the measurement of burnout, and prolonged emotional exhaustion can lead to depersonalization. Previous research on nurses’ burnout indicated that workload [ 20 ], job strain [ 9 , 10 , 11 ], morally injurious events [ 21 ], anxiety, and depression [ 22 ] positively affected burnout. Nurses with high levels of burnout were more prone to have higher turnover intention [ 23 , 24 ], lower job satisfaction [ 25 ] and organizational commitment [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies found that nurses’ episodic memories of PMIEs can have a unique negative association with their burnout, work motivation, work satisfaction, and adaptive performance several months after the event, mediated by autonomy thwarting [ 12 ]. Memories of self-PMIEs had stronger associations with burnout and turnover intentions compared to memories of other-PMIEs (i.e., enacted vs. witnessed PMIEs), mediated by the thwarting of all three basic psychological needs [ 13 ]. However, it remains unclear whether both memories of self-PMIEs and other-PMIEs would be associated with more burnout and turnover intentions when compared to a control group.…”
Section: Introductionmentioning
confidence: 99%
“…To date, protective factors against the negative effects of autobiographical episodic memories on psychological health and wellbeing have not been investigated, to the best of our knowledge. Previous findings suggest that nurses’ memories of PMIEs from the COVID-19 pandemic may not have yet been integrated in their autobiographical knowledge, an integration which might dramatically affect their work identities, behavior, and psychological health, with potential consequences on the healthcare organizational system [ 13 ]. Thus, departing from the mediating factors proposed, we set out to explore two potential moderators for the impact of memories of self- and other-PMIEs on burnout, turnover intentions, and work engagement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations